2021
DOI: 10.3346/jkms.2021.36.e188
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Cadaver Dissection during the COVID-19 Pandemic

Abstract: The rapid increase of the coronavirus disease 2019 pandemic from mid-February 2020 has led the anatomy department of the Korea University College of Medicine to cease the dissection laboratory. However, the hands-on anatomy laboratory experience is paramount to maximizing learning outcomes. In this paper, we share the experiences and lessons learned through the face-to-face cadaveric dissection experience during this disruptive situation. To minimize infection risks, the following strategies were applied: firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Also, most of the medical students felt that despite the solid knowledge gained through distance learning it would be crucial to complete cadaver dissections when they return. These findings were concordant with several other studies from across the world (Kim et al, 2021; Onigbinde et al, 2021; Papapanou et al, 2022). Although the dissection process was only via video demonstrations, the students reported gaining an understanding of anatomy content as well as abilities to carry out future dissections and to confidently locate structures quickly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, most of the medical students felt that despite the solid knowledge gained through distance learning it would be crucial to complete cadaver dissections when they return. These findings were concordant with several other studies from across the world (Kim et al, 2021; Onigbinde et al, 2021; Papapanou et al, 2022). Although the dissection process was only via video demonstrations, the students reported gaining an understanding of anatomy content as well as abilities to carry out future dissections and to confidently locate structures quickly.…”
Section: Discussionsupporting
confidence: 93%
“…Although the dissection process was only via video demonstrations, the students reported gaining an understanding of anatomy content as well as abilities to carry out future dissections and to confidently locate structures quickly. Writing the laboratory report was good for deepening their understanding of anatomy since they were able to correctly identify the location and relations of anatomical structures by taking screenshots and labeling structures in view, a method successfully used by others (Kim et al, 2021). However, data from focus group discussions revealed that most felt it increased the workload likely predisposing them to stress since anatomy was not the only subject being learned during the lockdown period.…”
Section: F I G U R Ementioning
confidence: 99%
“…Anatomy courses of medical students usually include comprehensive lectures in lecture halls and complete dissection of human bodies in laboratories (Gangata et al, 2010 ; Akinola, 2011 ). In particular, “hands‐on” dissection experience is important for medical students preparing to become surgeons to acquire surgical skills for future clinical practice (O'Leary et al, 2019 ; Li et al, 2020 ; Kim et al, 2021a ). The first Covid‐19 case in Taiwan was reported in January 2020, and learning practices had to be altered to follow Taiwan Centers for Disease Control guidelines (<60 people in a laboratory and a requirement to wear a mask) during the Covid‐19 pandemic (Liu et al, 2020 ; Cheng & Huang, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 The Lee Kong Chian School of Medicine in Singapore adopted a similar setup, 14 while the Korea University College of Medicine re-opened its dissection laboratory under strict public health protocols, reducing total anatomy laboratory hours to 85 in 2020 and 88 in 2021, from 96 hours in 2019. 15 The UP College of Medicine pioneered an enhancement program in anatomy and histology in the country. The LEAP is intended to provide a comprehensive laboratory experience where students are provided with anatomy learning materials in their physical form that will stimulate learners to retrieve prior knowledge from the virtual sessions, perform tasks (per station) in groups, plan and discuss application and relationship of each task to the overall understanding of anatomy.…”
Section: Discussionmentioning
confidence: 99%